Classical Hodgkin Lymphoma Arising Adjacent to a Breast Implant. (August 2016) - Ryan, Ciara; Ged, Yasser; Quinn, Fiona; Walker, Jan; Kennedy, John; Gillham, Charles; Pittaluga, Stefania; McDermott, Ronan; Vandenberghe, Elisabeth; Grant, Cliona; Flavin, Richard
Breast implant–associated lymphoma has recently gained wide recognition. Anaplastic large cell lymphoma (ALCL) is the most frequently diagnosed subtype in this setting but the spectrum is broadening. A 66-year-old woman developed swelling and itch around her saline implant 6 years after its insertion. Imaging revealed a fluid collection surrounding the implant with an adjacent mass. Microscopy showed sclerotic tissue punctuated by discrete cellular nodules comprising small lymphocytes, eosinophils and interspersed large atypical Hodgkin Reed-Sternberg (HRS)-like cells. The HRS-like cells stained positively for CD30 and CD15 by immunohistochemistry. Small T-lymphocytes formed rosettes around HRS-like cells. Appearances were consistent with classical Hodgkin lymphoma (HL). Multiplex polymerase chain reaction demonstrated no clonal rearrangements of immunoglobulin or T-cell receptor genes, however, a t(14;18)(q32;q21)BCL2-JH translocation involving the major breakpoint region of the bcl2 gene was present. Staging positron emission tomography–computed tomography scan revealed FDG-avid masses in the right axilla and pelvis. Subsequent pathological examination identified low-grade follicular lymphoma (FL) with a t(14;18) translocation at these sites. To our knowledge, this is the first case of HL arising adjacent to a breast implant. An awareness of this diagnosis is important as classical HL, with its prominent mixed inflammatory background, may be overlooked as a reactive process when histologically assessing capsulectomy specimens. It is also important in the differential diagnosis for implant-associated ALCL as both contain large atypical CD30-positive cells highlighting the need for full immunohistochemical and molecular workup in such cases. This case also adds to the large body of literature regarding the association between HL and FL.